Brilliant Blunders: From Darwin to Einstein — Colossal Mistakes by Great Scientists That Changed Our Understanding of Life and the Universe by Mario Livio - Bauer, Henry (Journal of Scientific Exploration, 2014)
<!--[if gte mso 9]> <![endif]--> This book gives accurate and nicely detailed descriptions, well worth reading, of the most significant theories or interpretations advanced by Darwin, Einstein, Hoyle, Kelvin, and Pauling. However, the designation of “blunder”, brilliant or not, seems unwarranted. What these tales illustrate instead is how difficult it is to get things perfectly and completely right the first time as knowledge is pushed beyond what’s already known. Darwin’s “blunder” was supposedly that he did not recognize a disconnect between his theory of natural selection and the contemporary ideas about transmission of heredity. So what? He generated a plausible theory, which has stood the test of time remarkably well, on the basis of a wealth of empirical data. Einstein’s blunder was his introduction of the cosmological constant to avoid predicting impossible expansion of the universe. Livio evidently looked into the common belief that Einstein himself pronounced this his greatest blunder and found the story to be apocryphal. But, again, substantively this was no blunder, just an attempt to square contemporary observations with theory. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] -->